Impact of Continuous Training to Improvement 21st Century Teacher Professionalism - Billy Martasandy Billy (Journal of Education and Teaching Learning, 2025)
Transformation education the 21st century demands that teachers have competence adaptive professional​ to development technology, application pedagogy innovative, as well as need participant continuous education​ developing. Research This aim For analyze influence training sustainable to improvement 21st century teacher professionalism in schools Senior High School (SMA) in Bandung Regency, West Java. Research use approach quantitative with method survey descriptive correlational. Population study totaling 185 high school teachers, while sample study a total of 120 teachers were determined use purposive sampling technique. Data collection technique carried out through questionnaire based Likert scale, observation, and documentation. Data analysis using statistics descriptive, normality test, linearity test, simple linear regression, hypothesis test, and coefficient determination with help SPSS application version 26. Research results show that training sustainable own influence significant to 21st century teacher professionalism with mark significance of 0.000 < 0.05. The equation regression obtained​ is : Y=32.417+0.633X. The result is show that every improvement training sustainable will increase teacher professionalism. Coefficient determination show contribution training sustainable to teacher professionalism is : R^2=0.562 or 56.2%, while the rest influenced other external factors research. Training sustainable proven capable increase competence digital pedagogy, creativity learning, ability collaboration, communication professional, as well as development teacher self in face challenge education 21st century. Therefore that, research This recommend strengthening sustainable, relevant teacher training programs with need learning, as well as integrated with development technology education to improve quality education in a way sustainable.